2020
DOI: 10.1111/cei.13432
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous interleukin-2 can rescue in-vitro T cell activation and proliferation in patients with a novel capping protein regulator and myosin 1 linker 2 mutation

Abstract: Capping protein regulator and myosin 1 linker 2 (CARMIL2) deficiency is characterized by impaired T cell activation, which is attributed to defective CD28-mediated co-signaling. Herein, we aimed to analyze the effect of exogenous interleukin (IL)-2 on in-vitro T cell activation and proliferation in a family with CARMIL2 deficiency. This study included four children (one male and three females; aged 2·5-10 years at presentation). The patients presented with inflammatory bowel disease and recurrent viral infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…All the described mutations were deleterious as they led to undetectable or reduced protein expression (P5) in CD4 + and CD8 + T cells, as measured by flow cytometry (Figure 2B). The current and previously reported mutations were located mostly in the LRR and HD domains, followed by the PH domain, 1,2,[11][12][13][14][15][16][17][18][19][20] and only one mutation in the CBR domain, 28 while mutations in PRR domain have not been identified. Despite undetectable CARMIL2 expression (regardless of mutation location), the clinical presentation varied in severity even between members of the same family.…”
Section: Genetic Analysis and Genotype/phenotype Assessmentsmentioning
confidence: 68%
See 2 more Smart Citations
“…All the described mutations were deleterious as they led to undetectable or reduced protein expression (P5) in CD4 + and CD8 + T cells, as measured by flow cytometry (Figure 2B). The current and previously reported mutations were located mostly in the LRR and HD domains, followed by the PH domain, 1,2,[11][12][13][14][15][16][17][18][19][20] and only one mutation in the CBR domain, 28 while mutations in PRR domain have not been identified. Despite undetectable CARMIL2 expression (regardless of mutation location), the clinical presentation varied in severity even between members of the same family.…”
Section: Genetic Analysis and Genotype/phenotype Assessmentsmentioning
confidence: 68%
“…All tested patients in our cohort had low Treg and cT FH cells, impaired proliferation in response to anti‐CD28, and low production of IL‐2, IL‐17, and IL‐21 cytokines after CD28 crosslinking. Importantly, the underlying defect was reported to be partially rescued by IL‐2 supplementation 2,15,19 . Compared to other CIDs with defective regulatory T‐cell functions, CARMIL2‐deficient patients exhibit much less autoimmune phenomenon 1,2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients present with low-level EBV-viremia. Interestingly, EBV-LPD or lymphoma has never been observed, instead 20% of the patients (8/44) developed EBV-associated smooth muscle tumors (SMT) [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. The mechanisms are still unknown.…”
Section: Carmil2 (Rltpr) Deficiencymentioning
confidence: 99%
“…This work emphasizes the need for timely diagnosis, optimal management and early referral for curative therapy. Another study from Shamriz et al, Editors' Choice in the June issue [14], showed that interleukin-2 can rescue T cell activation and proliferation in patients with capping protein regulator and myosin 1 linker 2 (CARMIL2) deficiency, which can manifest with immune dysregulation and increased rates of infection. The authors suggest that interleukin-2 should be studied further as a potential therapeutic model for these patients.…”
mentioning
confidence: 99%